Analysis of the Principles of Accountability and Transparency in the Management of School Operational Assistance Funds in SDN 117865 Afd. IV Perk. Berangir - Neni Indrayani; Kartika Sari Lubis (Sharia Economics Department Universitas KH. Abdul Chalim, Mojokerto, 2023)
The purpose of the research that has been carried out is to analyze the application of the principles of transparency and accountability in the preparation of BOS funds in SD Negeri 117865 Afd. IV Perk. Berangir, whose analysis supports the use of media in conveying information to the public. This study uses a qualitative approach method with a descriptive analysis method which is in accordance with the facts through a special study research design. In collecting the required data using data collection techniques such as observation, interviews, documentation, data condensation, data presentation, and data verification. Testing the validity of the data uses the credibility of transparency and accountability which involves all components including the school committee as the student’s guardian representative. In all management of School Operational Assistance (BOS) funds and responsibility for all activities that use BOS funds which are a source of education unit finance to the community by using the media in informing educational unit financial data both directly and indirectly, as well as increasing community participation which is the impact of implementing transparency and accountability.